2014
DOI: 10.1111/bij.12248
|View full text |Cite
|
Sign up to set email alerts
|

Colonization history of Mallorca Island by the European rabbit,Oryctolagus cuniculus, and the Iberian hare,Lepus granatensis(Lagomorpha: Leporidae)

Abstract: The Mediterranean islands have a long history of human‐mediated introductions resulting in frequent replacements of their fauna and flora. Although these histories are sometimes well documented or may be inferred from paleontological studies, the use of phylogenetic and population genetic reconstruction methods provides a complementary perspective for answering questions related to the history of insular species. In the present study, we infer the colonization history of Mallorca (Balearic Islands) by the Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Accordingly, Hardy et al (1994) reported on rabbits from Zembra (Tunisia), a Mediterranean island near Sicily, belonging to the O. c. cuniculus subspecies. In a more recent study, rabbits from the island of Mallorca were identified as belonging to O. c. cuniculus, having origins from Iberian and French populations (Seixas et al, 2014). Instead, the IP population in the northeast was regarded as O. c. cuniculus, whereas populations in the southwest of the IP, North Africa, the Mediterranean islands (including Sicily), and the Portuguese Atlantic islands were considered as O. c. algirus (Branco et al, 2000;Esteves et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Hardy et al (1994) reported on rabbits from Zembra (Tunisia), a Mediterranean island near Sicily, belonging to the O. c. cuniculus subspecies. In a more recent study, rabbits from the island of Mallorca were identified as belonging to O. c. cuniculus, having origins from Iberian and French populations (Seixas et al, 2014). Instead, the IP population in the northeast was regarded as O. c. cuniculus, whereas populations in the southwest of the IP, North Africa, the Mediterranean islands (including Sicily), and the Portuguese Atlantic islands were considered as O. c. algirus (Branco et al, 2000;Esteves et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The lowest diversity and high genetic differentiation found in the island of Mallorca is most likely due to the founder effect caused by the introduction of the rabbit in these Mediterranean islands following the first human arrival to Mallorca 4,300–4,100 years ago ( Flux, 1994 ; Alcover, 2008 ). Interestingly, a much older estimate has been proposed for the most recent common ancestor between island and mainland rabbits between 170,000 years and present, according to mitochondrial sequence data ( Seixas et al, 2014 ). While the number of alleles and allelic richness detected for Mallorca were lower than in most of the other samples analyzed, this was not the case for its heterozygosity values ( Table 1 and Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing Manuscript according to mitochondrial sequence data (Seixas et al, 2014). While the number of alleles and allelic richness detected for Mallorca were lower than in most of the other samples analyzed, this was not the case for its heterozygosity values (Table 1 and Supplementary Table 2).…”
Section: Variation In Genetic Diversitymentioning
confidence: 94%